STRUCTURAL ELEMENTS OF THE CULTURAL LEVEL – CONCEPT OF PERSONALITY - Sohibova Lola (American Journals, 2023)
This article analyzes scientific approaches to the content and structural elements of the cultural level of a person and the concept of cultural level. It has been philosophically analyzed that the level of awareness of national and universal human values, the standard of knowledge of humanistic ideas formed by mankind over the centuries, and the level of mastering social and professional knowledge are included in the set of structural elements of the cultural level of a person.
Keywords: Cultural level of a person, concept of cultural level, knowledge, idea, value, structural elements of cultural level of a person, main parameters.